Adenomyomatosis of the Gallbladder as a Cause of Recurrent Abdominal Pain. - Agrusti, Anna; Gregori, Massimo; Salviato, Tiziana; Codrich, Daniela; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abdominal Pain; Adenomyoma; Adolescent; Biopsy, Needle; Cholecystectomy; Diagnosis, Differential; Female; Gallbladder; Gallbladder Neoplasms; Humans; Immunohistochemistry; Recurrence; Risk Assessment; Severity of Illness Index; Ultrasonography, Doppler

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

What is known about deferasirox chelation therapy in pediatric HSCT recipients: two case reports of metabolic acidosis. - Fucile, Carmen; Mattioli, Francesca; Marini, Valeria; Gregori, Massimo; Sonzogni, Aurelio; Martelli, Antonietta; Maximova, Natalia (Ther Clin Risk Manag, 2018)
To date, in pediatric field, various hematological malignancies are increasingly treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). Iron overload and systemic siderosis often occur in this particular cohort of patients and are associated with poor prognosis. We describe herein the case of two allo-HSCT patients, on treatment with deferasirox; they showed histopathological elements compatible with venoocclusive disease or vanishing bile duct syndrome in ductopenic evolution before deferasirox started. The first patient developed drug-induced liver damage with metabolic acidosis and the second one a liver impairment with Fanconi syndrome. After withdrawing deferasirox treatment, both patients showed improvement. Measurements of drug plasma concentrations were performed by HPLC assay. The reduction and consequent disappearance of symptoms after the suspension of deferasirox substantiate its role in inducing hepatic damage, probably enabling the diagnosis of drug-induced liver damage. But the difficulties in diagnosing drug-related toxicity must be underlined, especially in compromised subjects. For these reasons, in patients requiring iron-chelating therapy, close and careful drug therapeutic monitoring is strongly recommended.

Hepatic Gadolinium Deposition and Reversibility after Contrast Agent-enhanced MR Imaging of Pediatric Hematopoietic Stem Cell Transplant Recipients. - Maximova, Natalia; Gregori, Massimo; Zennaro, Floriana; Sonzogni, Aurelio; Simeone, Roberto; Zanon, Davide (Radiology, 2016)
Purpose To determine if hepatic gadolinium deposition occurs in pediatric patients with iron overload but normal renal and hepatic function who undergo gadolinium-based contrast agent (GBCA)-enhanced magnetic resonance (MR) imaging. Materials and Methods Design and execution of this study was approved by the Ethical Committee of Institute for Research in Maternal and Child Health Burlo Garofolo of Trieste (reference no. 1105/2015). Because of the retrospective nature of the study, the requirement to obtain informed consent was waived. Twenty-one recipients of allogeneic hematopoietic stem cell transplants who underwent GBCA-enhanced MR imaging for suspected infection or relapse followed by liver biopsy comprised the study group. The number of GBCA-enhanced MR examinations and cumulative gadolinium dose for each patient was analyzed by comparing liver histologic analysis and iron and gadolinium liver concentration (GLC). Eight patients had siderosis and underwent chelation therapy. The study group was compared with four control patients who were never exposed to GBCA. Statistical analysis was performed with Spearman rank coefficient for correlation. Results All 21 patients had positive correlations between GLC and total GBCA dose (r = 0.4486; P < .05) and between GLC and liver iron concentration (r = 0.56; P < .05). Patients who underwent deferoxamine therapy had a significant reduction of GLC (from 0.64 μg/g ± 0.29 to 0.20 μg/g ± 0.17 [standard deviation]; P < .05). Conclusion In the presence of siderosis, a transmetallation mechanism may be set off between ferric ion and gadoterate meglumine. Deferoxamine appears capable of binding to gadolinium ion. Further studies of the safety of GBCAs in severe siderosis are needed. Chelation should be considered in patients with iron overload and a history of GBCA exposure. (©) RSNA, 2016.

"Safety and utility of percutaneous liver biopsy in hematopoietic stem cell transplant pediatric recipients: a retrospective study". - Maximova, Natalia; Gregori, Massimo; Barbieri, Francesca; Pizzol, Antonio; Sonzogni, Aurelio (BMC Cancer, 2016)
BACKGROUND: Liver biopsies in pediatric hematopoietic stem cell transplantation (HSCT) patients are as and effective when performed at bedside in the Bone Marrow Transplant Unit (BMTU) than in the Day Surgery Unit (DSU), with better patient compliance and lower emotional distress for these children. METHODS: The study group consisted of 45 children who underwent allogeneic HSCT. We reviewed 68 liver biopsies performed between April 2006 and September 2015. 12 (17.6 %) biopsies were performed in the DSU and 56 (82.3 %) in the BMTU; nine (13.2 %) prior to HSCT and 59 (86.7 %) after HSCT. Pre-procedural behavioral status (subjective score) was evaluated by pediatric transplant physicians by filling in a questionnaire employing a three-point scale: "calm and cooperative", "agitated and non-cooperative" or "frightened and suffering". Objective score was obtained measuring patient's heart rate before the procedure and comparing it with mean heart rate. RESULTS: Patients who underwent the procedure at the BMTU experienced less emotional distress than those who underwent it in the DSU: 58.3 % of patients treated at the DSU were agitated as compared with 16.1 % of those treated at the BMTU (p < 0.01). Among the 59 biopsies performed after HSCT, 41 (69.5 %) were taken from symptomatic patients for a diagnostic purpose and 18 (30.5 %) in asymptomatic ones in order to rule out hepatic GVHD. Among these 18 procedures, GVHD was diagnosed in 16 (88.9 %) cases. Minor complications occurred in about 17 % of procedures (12 biopsies), at a rate of 25 % for the DSU location compared with 16 % for the BMTU location. Only two major complications were reported, one in the DSU and one in the BMTU. CONCLUSION: Liver biopsy performed at bedside in HSCT patients does not carry a higher risk of adverse events than the same procedure performed in the DSU and has lower emotional distress associated with better patient compliance, thus contributing significantly to a higher standard of care.

Handlebar injury in children: The hidden danger. - Pederiva, Federica; Guida, Edoardo; Maschio, Massimo; Rigamonti, Waifro; Gregori, Massimo; Codrich, Daniela (Surgery, 2015)

Metal accumulation in the renal cortex of a pediatric patient with sickle cell disease: a case report and review of the literature. - Maximova, Natalia; Zanon, Davide; Pascolo, Lorella; Zennaro, Floriana; Gregori, Massimo; Grosso, Daniele; Sonzogni, Aurelio (J Pediatr Hematol Oncol, 2015)
BACKGROUND: Sickle cell disease (SCD) is a well-known multisystem illness characterized by vascular injury due to vasoocclusion and hemolysis, as well as infectious complications and iron overload, all of which contribute to high morbidity and mortality rates among children. In these patients, some authors have previously described iron cortical deposition in the kidney. We here report the first case in the literature of a girl affected by SCD showing an anomalous metal and rare element retention in the renal cortex. CASE PRESENTATION: A 10-year-old white girl affected by SCD underwent a routine magnetic resonance imaging investigation that evidenced a reduced signal intensity in the renal cortex, compatible with hemosiderin precipitation. Histologic and elemental analyses of the hepatic and the renal biotic samples, performed with inductively coupled plasma mass spectrometry, revealed that concomitant with the high iron deposition, toxic and potentially carcinogenic elements such as nickel, magnesium, rubidium, and gadolinuim were anomalously retained particularly in the kidney. CONCLUSIONS: The finding of rare and toxic elements in the kidney of SCD patients might be linked to the development of specific neoplastic transformations already described in this patient cohort. To be confirmed, our speculations need to be demonstrated in large sampling of patients.
Keywords: Anemia, Sickle Cell; Child; Female; Humans; Kidney Cortex; Metals; Spectrophotometry, Atomic

Polyclonal gammopathy after BKV infection in HSCT recipient: a novel trigger for plasma cells replication? - Maximova, Natalia; Pizzol, Antonio; Sonzogni, Aurelio; Gregori, Massimo; Granzotto, Marilena; Tamaro, Paolo (Virol J, 2015)
BACKGROUND: BK polyomavirus infects most of the general population. However, its clinical manifestations are almost exclusively seen in immunocompromised patients, particularly in kidney and hematopoietic stem cell transplantation recipients. CASE PRESENTATION: A 15-y-old female suffering from common B-cell acute lymphoblastic leukaemia underwent hematopoietic stem cell transplantation. The patient had reactivation of BKPyV infection and developed an haemorrhagic cystitis. Three months after transplant, BKPyV viremia and viruria increased and she developed a severe nephropathy associated to a polyclonal gammopathy with high levels of isolated IgM. CONCLUSION: This case report describes a rare and unexpected polyclonal gammopathy developed during a polyomavirus-associated nephropathy confirmed by immunohistochemical and laboratory analyses.

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical